Aid, environment, and climate change in Africa: The case of Senegal - Tidiane Ngaido (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
The paper reviews the dynamics of the financing baseed its analysis on the rich dataset of AidData ranging over 1993-2010, with around 9,077 observations on projects funded in Senegal by various multilateral as well as bilateral donors. The study started in the same year as the establishment of the environment ministry, 1993, to assess the perspectives as well as the evolution of the financing of the environment. Such an approach has large benefits as it helps to (1) capture changes in financial commitments and disbursement within and across sectors; (2) show the composition and changes of the portfolio of donors and levels of funding in the sector; (3) document which subsectors of the environment are receiving more resources; and (4) demonstrate effects achieved to date.
Keywords: F34; F35; O13; H6; 330; aid; biodiversity; climate change; environment; financing